2016
DOI: 10.1038/ncomms10777
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol phosphate kinase PIPKIγ and phosphatase INPP5E coordinate initiation of ciliogenesis

Abstract: Defective primary cilia are causative to a wide spectrum of human genetic disorders, termed ciliopathies. Although the regulation of ciliogenesis is intensively studied, how it is initiated remains unclear. Here we show that type Iγ phosphatidylinositol 4-phosphate (PtdIns(4)P) 5-kinase (PIPKIγ) and inositol polyphosphate-5-phosphatase E (INPP5E), a Joubert syndrome protein, localize to the centrosome and coordinate the initiation of ciliogenesis. PIPKIγ counteracts INPP5E in regulating tau-tubulin kinase-2 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 56 publications
7
110
0
Order By: Relevance
“…Phosphatidylinositol (PtdIns) homeostasis and phosphorylation at the basal body are also linked with TTBK2 regulation and ciliogenesis 44 . Intriguingly, the balance of two activities — a PtdIns kinase (PIPKIγ) and an opposing phosphatase (INPP5E) — fine-tunes PtdIns(4)P and PtdIns(4,5)P 2 levels.…”
Section: Basal Body Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidylinositol (PtdIns) homeostasis and phosphorylation at the basal body are also linked with TTBK2 regulation and ciliogenesis 44 . Intriguingly, the balance of two activities — a PtdIns kinase (PIPKIγ) and an opposing phosphatase (INPP5E) — fine-tunes PtdIns(4)P and PtdIns(4,5)P 2 levels.…”
Section: Basal Body Dockingmentioning
confidence: 99%
“…Given that acetylation of cortactin abrogates its interaction with filamentous actin and that actin polymerization counteracts cilium assembly, de-acetylation of cortactin could further explain how HDAC6 activation promotes cilium disassembly by enhancing actin polymerization. Apart from its role as an HDAC6 regulator, Aurora A also activates INPP5E 55 , which would favour high levels of PtdIns(4)P and suppress ciliogenesis through a second mechanism 44 .…”
Section: Cilium Disassemblymentioning
confidence: 99%
“…Both groups showed that localization of active INPP5E to the cilium is required to generate a membrane environment enriched in PI(4)P and that this lipid environment restricts the ciliary localization of two negative regulators of Hedgehog signaling, Tulp3 and Gpr161 [69**,70**]. Xu et al showed that the 5-phosphatase function of INPP5E is counteracted by the PI4P 5-kinase PIPKIγ and that enrichment of PI(4,5)P 2 at the base of the cilium is critical for ciliogenesis [71**]. A PI(4,5)P 2 -enriched zone at the base of the cilium has also been found in T. brucei and C. elegans [53**,72].…”
Section: Generating a Unique Ciliary Lipid Contentmentioning
confidence: 99%
“…With the intimate connection between Gle1 and components of the inositol signaling Ipk1/IP 6 and the importance of inositol pathways in cell and developmental signaling (Bielas et al. , 2009; Sarmah and Wente, 2010; Xu et al. , 2016), an exciting future challenge is to further elucidate the interplay between RNA metabolism, Gle1, and inositol signaling at the centrosome and basal body.…”
Section: Discussionmentioning
confidence: 99%